A three-dimensional porous MoS2–PVP aerogel as a highly efficient and recyclable sorbent for oils and organic solvents. Issue 4 (18th June 2020) - Song, Pin; Di, Jun; Chen, Haiping; Zhao, Sirui; Wu, Cao; Cao, Xun; Wang, Meiling; Xiong, Jun; Ye, Xinli
Abstract : Three-dimensional (3D) aerogels have attracted more and more attention in oil–water separation, due to their advantages of low density, high porosity, and large specific surface area. Abstract : Three-dimensional (3D) aerogels have attracted more and more attention in oil–water separation, due to their advantages of low density, high porosity, and large specific surface area. However, their application is greatly limited due to their hydrophilic and low adsorption properties. In this work, we report a 3D MoS2 –polyvinylpyrrolidone (PVP) aerogel, prepared by a freeze-drying method, where PVP was used as a skeleton to support the aerogel. As a surfactant, PVP can easily attach to the surface of MoS2 nanosheets and facilitate the interconnection between nanosheets. The 3D MoS2 –PVP aerogel exhibits low density, high porosity, good hydrophobicity, and excellent adsorption capacity (195–649 times). Moreover, after 30 cycles, the structure of the 3D MoS2 –PVP aerogel is well kept and the adsorption capacity is still retained, at 93.5% and 92.9%, by squeezing and distillation, respectively. Therefore, the obtained 3D MoS2 –PVP aerogel is a promising adsorption material and has great practical application potential in oil–water separation.